The condor trials: transnational repression and human rights in South America - Lessa, Francesca (Yale University Press, 2022)
Through the voices of survivors and witnesses, human rights activists, judicial actors, journalists, and historians, Francesca Lessa unravels the secrets of transnational repression masterminded by South American dictators between 1969 and 1981. Under Operation Condor, their violent and oppressive regimes kidnapped, tortured, and murdered hundreds of exiles, or forcibly returned them to the countries from which they had fled. South America became a zone of terror for those who were targeted, and of impunity for those who perpetuated the violence. Lessa shows how networks of justice seekers gradually materialized and effectively transcended national borders to achieve justice for the victims of these horrors. Based on extensive fieldwork, archival research, trial ethnography, and over one-hundred interviews, The Condor Trials explores South America’s past and present and sheds light on ongoing struggles for justice as its societies come to terms with the unparalleled atrocities of their not-so-distant pasts.